Situating Human Rights Violation Narratives in the Tragedy of the FPI Militia Shooting Incident in the Film 'Kilometer 50’ - Dwyangghara, Muhammad Arief; Maryani, Eni; Mirawati, Ira (UNIVERSITAS PAKUAN, 2019)
The documentary film